Review of complications due to foramen ovale puncture - Kaplan, Metin; Erol, Fatih Serhat; Ozveren, Mehmet Falk; Topsakal, Cahide; Sam, Bulent; Tekdemir, Ibrahim (Elsevier Sci Ltd, 2007)
We aim to evaluate the mechanisms responsible for complications during trigeminal rhizotomy via foramen ovale puncture. Ten dry skulls and 10 skull-base specimens were investigated in the present study. In cadaveric skull-base specimens, the anatomical relationships between the foramen ovale, mandibular nerve and Gasserian ganglion and the surrounding neurovascular structures were investigated intradurally. The distance between the foramen ovale and Gasserian ganglion was measured as 6 rum. The abducent nerve, adjacent to the anterior tail of the petrolingual ligament, was observed passing along the lateral wall of the cavernous sinus. Advancement of the catheter more than 10 mm from the foramen ovale is likely to damage the internal carotid artery and the abducent nerve at the medial side of the petrolingual ligament. Thermocoagulation of the lateral wall of the cavernous sinus may damage the cranial nerves by heat, giving rise to pareses. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: complications; cranial nerves; foramen ovale; trigeminal rhizotomy